ANALISIS PENDAPATAN AGROINDUSTRI KERIPIK NENAS DAN KERIPIK NANGKA DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Kamal, Samsul; Tety, Ermi; Tarumun, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims to analyze the income of pineapple chips and jackfruit chips agroindustrial besiness in Kualu Nenas Village Tambang District Kampar Regency. Datas which used in thid research are primary data and secondary data. Method which used in this research was census method with 11 respondents. This research used descriptive analysis, cost and income analysis, break-even point (BEP) analysis, and business efficiency (RCR) analysis. The result showed that pineapple chips and jackfruit chips agroindustrial business already profitable. An average of 11 businessman ear net income of pineapple chips and jackfruit chips each of Rp. 6.471.896,32 per month and Rp. 1.289.921,91 per month. The processing efficiency of pineapple and jackfruit into pineapple chips and jackfruit chips each of 1,36 dan 1,90. The agroindustrial business experienced a break-even point (BEP) in production unit when producing 96,15 kg pineapple chips per month and break-even point (BEP) in sale unit equal to Rp. 10.838.301,59. While the break-even point (BEP) in production unit of jackfruit chips experienced when producing 6,33 kg jackfruit chips per month and break-even point (BEP) in sale unit equal to Rp. 915.321,50. Â Keywords : Agroindustry, Break Event Point, Business Efficiency, Income